Hip fractures in elderly patients with non-dialysis dependent chronic kidney disease: Outcomes in a Southeast Asian population. Issue 27 (9th July 2021) - Roy, Debajyoti; Pande, Shrikant; Thalanki, Srikiran; Yeon, Wenxiang; Prasad, Ankit; Lau, Adrian; Varman, Surendra; Carson, John Allen
Abstract : Abstract: Chronic kidney disease (CKD) causes bone and mineral disorders and alterations in vitamin D metabolism that contribute to greater skeletal fragility. Hip fracture in elderly is associated with significant morbidity and mortality. The aim of this study was to investigate the outcome of elderly patients with non-dialysis dependent CKD and hip fracture undergoing surgery. Retrospective study with IRB approval of patients above 65 years of age, with hip fractures admitted between June 2014 to June 2016 in a Southeast Asian cohort. Data collected included demographic variables and the haematological and biochemical parameters HBA1c, estimated glomerular filtration rate (eGFR), serum calcium, phosphorous, and 25(OH) Vitamin D. Co-morbidities investigated were ischemic heart disease, congestive heart failure, peripheral vascular disease, malignancy, chronic obstructive pulmonary disease, cerebro vascular accident, hypertension and hyperlipidaemia. All patients were followed up from index date to either death or June 1, 2018. Of the 883 patients, 725 underwent surgery and 334 had CKD. Death rates for CKD patients with hip fractures and those with normal renal function did not differ significantly [8.08% vs 6.54%, (HR= 1.33, 95% CI: 0.95, 1.86; P  = .102)], whilst median hospital length of stay was significantly higher in CKD patients [10.5 vs 9.03 days ( P  = .003)]. Significant risk factors associated with higher risk of mortality in the elderly with hip fracture were male gender, age ≥80 years and serum albumin < 30 g/L (all, P  < .0001). In summary, in elderly, non-dialysis dependent CKD patient with hip fracture we found that male gender, age ≥80 years, low serum albumin and eGFR < 30 mL/min/1.73 m 2 were associated with higher risk of death. The hospital stay in the CKD group was also longer. Additional studies are needed to validate our findings.